PERAN STRUKTUR MODAL, PROFITABILITAS, DAN KEBIJAKAN DIVIDEN TERHADAP HARGA SAHAM - Vina Wahyuning Triyas; Linda Ayu Oktoriza; Lenni Yovita; Vicky Oktavia (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research aims to export the impact of Capital Structure, Profitability, and Dividend Policy on Stock Prices in banking sub-sector issuers verified on the Indonesia Stock Exchange in 2019-2023. Method: This research is a quantitative study using secondary data with the population being banking sub-sector issuers verified on the IDX in 2019-202 and sampling using purposive sampling, thus determining 22 samples that meet the criteria. The data analysis method uses multiple linear regression analysis with the help of the IBM SPSS Statistics program. Results: The output of this research reveals that Capital Structure, Profitability, and Dividend Policy simultaneously have a significant effect on Stock Prices. Partially, all variables, namely Capital Structure, Profitability, and Dividend Policy, have a significant positive effect on Stock Prices in banking sub-sector companies listed on the Indonesia Stock Exchange in 2019-2023. Conclusion and suggestions: Capital Structure as measured by Debt to Equity Ratio (DER), Profitability as measured by Return on Asset (ROA), and Dividend Policy as measured by Dividend Payout Ratio (DPR) have a significant positive effect on stock prices in banking issuers verified on the Indonesia Stock Exchange in 2019-2023. Therefore, Hypothesis 1 to Hypothesis 4 are accepted. Further research, is expected to consider other proxy variables in this research besides the variables used by the author in this research that can affect stock prices. Keywords: Capital Structure, Profitability, Dividend Policy, Stock Price